Food regulation : law, science, policy, and practice - Fortin, Neal D. (John Wiley & Sons, 2009)
Food Regulation: Law, Science, Policy, and Practice provides an in-depth discussion of the federal statutes, regulations, and regulatory agencies involved in food regulation. After an introduction to U.S. food and drug regulation, it covers current food regulations, inspection and enforcement, international law, the Internet, and ethics